Depression as seen and Managed in a Sentinel Network of General/Family Practitioners - T.Y. Thunemann; Pierre J.T. de Villiers (South African Family Practice)
Aim of the study: To determine the diagnostic criteria used and initial management followed by general practitioners in the diagnosis and management of depression. Study design and setting: A prospective descriptive survey by general practitioners of a Sentinel research network in South Africa. Methods: Thirty-five members of SASPREN, during a three month period in 1993, completed a questionnaire about each patient seen with the diagnosis of a depressive disorder. The questionnaire included socio-demographic details of the patient, the reason(s)for encounter (RFE), the diagnostic criteria used by the practitioner, the degree of functional impairment of the patient as well as details of the initial management regimen followed by the practitioner. Results: Twenty-three practitioners responded with completed questionnaires. Twenty-two practitioners were from the private sector and 78% worked in metropolitan areas. They reported 159 newly-diagnosed cases of depression from 30 958 patient encounters (5,14 per I 000 encounters). Seventy-four per cent of the patients were female. Sixty-two per cent were married and, 68% had secondary school or higher education. An average of 2,5 RFE were recorded per patient, the most common being depressed mood (36%), pain (25%) and fatigue (23%). An average of 4,4 diagnostic criteria were recorded per patient. Only 24 (15%) met the DSM-III-R criteria for a major depressive disorder. Thirty-six (23%) suffered from a debilitating condition and, l7% had lost a loved one recently. Eighty per cent received pharmacological therapy for depression, of which 38% were tricyclic antidepressants and 18% serotonin re-uptake inhibitors. Seventy-nine per cent were followed-up by the GPs and 11% were referred to other professionals while 3% were hospitalised. Conclusions: Depression presents with a very broad spectrum of RFE in general practice. The majority of GPs do not follow the diagnostic criteria intended for use in primary care, pointing to possible shortcomings of these definitions. Pharmacotherapy was very readily prescribed, with antidepressants used most often, in contrast to findings to the contrary in previous studies.